The Standardization Transformation of Industry Oriented Batik to Accelerate Competitiveness 4.0 and National Independence in Clothing Sector during New Normal - WIDIANA, Muslichah Erma (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021, 2021)
C OVID -9 pandemic has occurred around the world including Indonesia. All Indonesian people fought C OVID -19 with a lockdown. It was a regional quarantine policy by means of Large-Scale Social Restrictions and Enforcement of Restrictions on Community Activities. This limitation due to the C OVID -19 pandemic causes the slowdown of economy of Indonesia and other countries around the world. This economic slowdown is comprehensive in all fields, including the batik business sector. At present, the Indonesian government is trying to implement a new normal policy. Thus, the economic impact caused by the pandemic does not cause a prolonged crisis. This research aimed to find a business strategy in the transformation of industry-oriented batik standardization to accelerate competitiveness 4.0 and national independence in the new-normal period of clothing sector. The method used to overcome the above problems was descriptive qualitative method. Data was collected through literature review, in-depth observation, and direct practice. Research results: business strategies that could be carried out in the transformation of batik standardization in welcoming the new normal era were: 1. Creating innovation 2. Development/recognition of existing products such as printing batik, jumputan batik or tie dye batik, and Eco print batik 3. Creating a new economic market by implementing the Blue Ocean strategy. 4 Paying attention to opportunities during the new normal 5. Developing a strategic marketing plan 6. Maintaining good communication with customers by utilizing social media, and 6. Promotion and marketing on line. This research is expected to be useful for readers, researchers, and the batik industry in responding to the new normal conditions after 1 (one) year of being hit by the C OVID -19 pandemic.